2015
DOI: 10.1007/s10096-015-2442-6
|View full text |Cite
|
Sign up to set email alerts
|

Dientamoeba fragilis prevalence coincides with gastrointestinal symptoms in children less than 11 years old in Sweden

Abstract: Dientamoeba fragilis is a protozoan with a debated role in gastrointestinal (GI) disease. Although correlated to GI symptoms, no virulence factors have been described. In this study, we evaluated the cause of GI symptoms in children at two schools, with children aged 1 to 10 years, in the county of Jönköping, Sweden. D. fragilis infection correlated to GI symptoms in children and Enterobius vermicularis correlated to D. fragilis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
0
18
1
1
Order By: Relevance
“…A more comprehensive study with a broad age distribution is needed to resolve this issue. These limitations aside, this finding is similar to studies showing trends of higher infection rates in adults [9,14,37] and in contrast to some reports suggesting that children are common D. fragilis carriers [9,[38][39][40]. Other studies have shown no influence of gender or age on rates of D. fragilis infection [10,27].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A more comprehensive study with a broad age distribution is needed to resolve this issue. These limitations aside, this finding is similar to studies showing trends of higher infection rates in adults [9,14,37] and in contrast to some reports suggesting that children are common D. fragilis carriers [9,[38][39][40]. Other studies have shown no influence of gender or age on rates of D. fragilis infection [10,27].…”
Section: Discussioncontrasting
confidence: 54%
“…Many studies have shown correlation of infection with D. fragilis and clinical symptoms [3,8,9,13,39], while others report no relationship between symptomatic infection and this parasite [44][45][46]. This disparity is not surprising, as manifestations ranging from subclinical to severe gastrointestinal symptoms is typically observed in parasitic enteropathogen infections.…”
Section: Discussionmentioning
confidence: 72%
“…Dientamoeba was associated with diarrhea, fever, vomiting, and abdominal pain in this patient group (99). Ogren et al (124) found an association between D. fragilis and GI symptoms in children aged 1 to 10 years from the county of Jönköping, Sweden.…”
Section: Clinical Aspects and Epidemiologymentioning
confidence: 99%
“…Organisms seen in direct wet mounts may appear as refractile, round forms; the nuclear structure cannot be seen without examination of the permanent stained smear. It has also been confirmed that molecular methods are far more sensitive than wet mounts (36). With the recent confirmation of the cyst stage, one needs to take into account the more shrunken appearance of this form compared with the trophozoite.…”
Section: Diagnosismentioning
confidence: 99%